Analysis and Reconstruction of Student Practicum Worksheets on Food Carbohydrate Testing - Ghurrotul Bariroh; Widi Purwianingsih; Kusnadi (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Practicum worksheets are a tool used by students to increase their understanding of various biological concepts through experiments and direct observation. However, there are many biology practicum worksheets used today often do not meet the appropriate standards. Therefore, this research aims to analyze conceptual, procedural, and knowledge construction aspects based on vee diagrams on students' practicum worksheets. The method used in this research is qualitative-descriptive. The samples were selected using purposive sampling so that six samples of practicum worksheets for phase F students in the Merdeka Curriculum were obtained with material testing carbohydrates in food. The research results show that conceptually, the practicum content is not in accordance with the learning outcomes in the Merdeka Curriculum. Procedurally, the practicum worksheets still need to be improved in terms of tools, materials, procedures, phenomenon objects, and data recording. This has an impact on students' difficulties in constructing their knowledge. It is hoped that the results of the reconstruction of practicum worksheets based on conceptual, procedural, and knowledge construction analysis can be used as a reference and basis for teachers in designing practicum activities specifically on digestive system material.